Development of the Electromagnetic Regenerative Shock Absorber as an Energy Harvesting Tool for Vehicles - Wanda Afnison; Erzeddin Alwi; Hasan Maksum; Bahrul Amin; M Yasep Setiawan (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
This research is a development of previous research entitled